Gaya Kepemimpinan Pengelola Pusat Kegiatan Belajar Masyarakat (PKBM) Bintang Flobamora Kota Kupang - Maukari, Norince Patriana; Neonufa, Samrid; Lima, Stofiani Susana (Universitas Nusa Cendana, 2025)
The leadership style of a leader reflects how they act, behave, or present themselves when in control. Depending on the situation, leaders may adopt different styles. Leadership style refers to the approach used by a leader in directing, motivating, and managing a team to achieve specific goals. It reflects the leader’s character, values, and communication methods in decision-making and managing relationships with subordinates.This study aims to identify the leadership style of the PKBM (Community Learning Center) manager in developing PKBM Bintang Flobamora in Kupang City. A qualitative descriptive approach was used, involving six research subjects. Data were collected through interviews, documentation, and observation. Data analysis included collection, reduction, presentation, and conclusion drawing. Source and methodological triangulation were used to ensure data validity.The study found four main leadership styles applied by the manager:(1) Democratic: Involves staff in decision-making, encourages collaborative problem-solving, works closely with subordinates, and maintains strong communication. (2) Charismatic: Uses persuasive communication to inspire staff, applies appropriate language, engages effectively in meetings, and provides motivational support. (3) Authoritarian: Makes independent decisions only in urgent situations that require immediate action, while explaining the rationale afterward.(4) Moralistic: Demonstrates concern for staff development, listens to complaints, and fosters a respectful and supportive work environment.